Gender-transformative Bandebereho couples’ intervention to promote male engagement in reproductive and maternal health and violence prevention in Rwanda: Findings from a randomized controlled trial - Doyle, Kate (PLoS One, 2018)
BACKGROUND: Rigorous evidence of the effectiveness of male engagement interventions, particularly on how these interventions impact relationship power dynamics and women’s decision-making, remains limited. This study assessed the impact of the Bandebereho gender-transformative couples’ intervention on impact on multiple behavioral and health-related outcomes influenced by gender norms and power relations. METHODS: We conducted a multi-site randomised controlled trial in four Rwandan districts with expectant/current fathers and their partners, who were randomised to the intervention (n = 575 couples) or control group (n = 624 couples). Primary outcomes include women’s experience of physical and sexual IPV, women’s attendance and men’s accompaniment at ANC, modern contraceptive use, and partner support during pregnancy. At 21-months post-baseline, 1123 men and 1162 partners were included in intention to treat analysis. Generalized estimating equations with robust standard errors were used to fit the models. FINDINGS: The Bandebereho intervention led to substantial improvements in multiple reported outcomes. Compared to the control group, women in the intervention group reported: less past-year physical (OR 0.37, p<0.001) and sexual IPV (OR 0.34, p<0.001); and greater attendance (IRR 1.09, p<0.001) and male accompaniment at antenatal care (IRR 1.50, p<0.001); and women and men in the intervention group reported: less child physical punishment (women: OR 0.56, p = 0.001; men: OR 0.66, p = 0.005); greater modern contraceptive use (women: OR 1.53, p = 0.004; men: OR 1.65, p = 0.001); higher levels of men’s participation in childcare and household tasks (women: beta 0.39, p<0.001; men: beta 0.33, p<0.001); and less dominance of men in decision-making. CONCLUSIONS: Our study strengthens the existing evidence on male engagement approaches; together with earlier studies our findings suggest that culturally adapted gender-transformative interventions with men and couples can be effective at changing deeply entrenched gender inequalities and a range of health-related behavioral outcomes. TRIAL REGISTRATION: ClinicalTrials.gov NCT02694627